PENERAPAN TERAPI RENDAM KAKI DENGAN AIR HANGAT TERHADAP INSOMNIA PADA LANSIA DI WILAYAH BINAAN PUSKESMAS ROWOSARI SEMARANG: THE IMPLEMENTATION OF FOOT SOAK THERAPY WITH WARM WATER TOWARDS INSOMNIA IN ELDERLY IN THE REGION OF PUSKESMAS ROWOSARI SEMARANG - Sri Rahmah Putri Nirmala; Novita Wulan Sari (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2021)
Elderly is an end stage in the span of human life. Age that is not young makes the elderly vulnerable to degenerative diseases such as insomnia. Insomnia is a condition where a person has difficulty sleeping, especially sleeping at night. Foot soak therapy is a therapy using warm water which aims to overcome insomnia. The purpose of this case study is to describe the application of foot bath therapy with warm water to insomnia in the elderly. This type of research belongs to descriptive using the case study approach method. The subjects used were two respondents with criteria for elderly who were over 60 years old and experienced mild, moderate and severe insomnia. The form of intervention was the application of foot soak therapy with warm water for 2 days. The measuring instrument used was an insomnia rating scale questionnaire. The results of the case study showed that there was a decrease in the score of insomnia after doing foot bath therapy with warm water, proven in subject I from a score of 28 (weight) to a score of 25 (mild) and in subject II from a score of 26 (mild) to a score of 24 (mild).